Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{1}{2}\times\frac{1}{3}\times\frac{1}{4}=\frac{1\times1\times1}{2\times3\times4}=\frac{1}{24}\)
\(\frac{1}{2}\times\frac{1}{3}\div\frac{1}{4}=\frac{1}{2}\times\frac{1}{3}\times\frac{4}{1}=\frac{1\times1\times4}{2\times3\times1}=\frac{4}{6}=\frac{2}{3}\)
\(\frac{1}{2}\div\frac{1}{3}\times\frac{1}{4}=\frac{1}{2}\times\frac{3}{1}\times\frac{1}{4}=\frac{1\times3\times1}{2\times1\times4}=\frac{3}{8}\)
\(\frac{2}{5}+1=\frac{2}{5}+\frac{5}{5}=\frac{7}{5}\) ;\(\frac{6}{7}.4=\frac{24}{7}\);\(\frac{3}{7}:2=\frac{3}{7}.\frac{1}{2}=\frac{3}{14}\);\(2:\frac{2}{4}=2.\frac{4}{2}=2.2=4\);\(\frac{3}{4}.4+\frac{1}{3}=\frac{12}{4}+\frac{1}{3}=3+\frac{1}{3}=\frac{10}{3}\);\(\frac{1}{4}:\frac{1}{3}-\frac{1}{2}=\frac{1}{4}.\frac{3}{1}-\frac{1}{2}=\frac{3}{4}-\frac{1}{2}=\frac{1}{4}\)
\(\frac{2}{5}+1=\frac{2}{5}+\frac{5}{5}=\frac{7}{5}\)
\(\frac{6}{7}\times4=\frac{6\times4}{7}=\frac{24}{7}\)
\(\frac{3}{7}\div2=\frac{3}{7}\times\frac{1}{2}=\frac{3\times1}{7\times2}=\frac{3}{14}\)
\(2\div\frac{2}{4}=2\times\frac{4}{2}=2\times2=4\)
\(\frac{3}{4}\times4+\frac{1}{3}=\frac{3\times4}{4}+\frac{1}{3}=3+\frac{1}{3}=\frac{9}{3}+\frac{1}{3}=\frac{10}{3}\)
\(\frac{1}{4}\div\frac{1}{3}-\frac{1}{2}=\frac{1}{4}\times3-\frac{1}{2}=\frac{1\times3}{4}-\frac{1}{2}=\frac{3}{4}-\frac{1}{2}=\frac{3}{4}-\frac{2}{4}=\frac{1}{4}\)
Bài 1
1/2 x 3/4 : 4/5
= 3/8 : 4/5
= 3/8 x 5/4
= 15/32
2/3 + 1/6 - 1/2
= 4/6 + 1/6 - 3/6
= 5/6 - 3/6
= 1/3
3/5 + 4 : 2/3 - 3/2
= 3/5 + 4 x 3/2 - 3/2
= 3/5 + 6 - 3/2
= 3/5 + 30/5 - 3/2
= 33/5 - 3/2
= 66/10 - 15/10
= 28/5
Bài 2
x - 1/4 = 1/2
x = 1/2 + 1/4
x = 2/4 + 1/4
x = 3/4
2/3 + x = 1
x = 1 - 2/3
x = 3/3 - 2/3
x = 1/3
\(\dfrac{1}{2}\times\dfrac{1}{3}+\dfrac{1}{4}\)
\(=\dfrac{1}{2}\times\dfrac{4}{12}+\dfrac{3}{12}\)
\(=\dfrac{1}{2}\times\dfrac{7}{12}\)
\(=\dfrac{7}{24}\)
\(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}=\dfrac{6}{12}+\dfrac{4}{12}+\dfrac{3}{12}=\dfrac{6+4+3}{12}=\dfrac{13}{12}\)